2019
DOI: 10.1111/andr.12658
|View full text |Cite
|
Sign up to set email alerts
|

IGF signalling in germ cells and testicular germ cell tumours: roles and therapeutic approaches

Abstract: The insulin‐like growth factor (IGF) axis plays key roles in normal tissue growth and development as well as in the progression of several tumour types and their subsequent growth and progression to a metastatic phenotype. This review explores the role of IGF system in normal germ cell development and function in addition to examining the evidence for deregulation of IGF signalling in cancer, with particular relevance to evidence supporting a role in testicular germ cell tumours (TGCTs). Despite the clear prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 106 publications
1
4
0
1
Order By: Relevance
“…However, the reported results of the NT2D1 cell invasion assays strongly indicate that the autologous microenvironment could positively or negatively modulate the cellular response to pathway inhibitors, and should be studied as a fundamental co-factor necessary for the success of inhibitor-based therapies. Taken together, these results indicate that the study of the testicular secretome of TGCT patients could be a useful tool to identify the possible interaction among PI3K inhibitors, i.e., those used for the targeted therapy proposed by [ 26 ] Selfe and coworkers, and the signaling pathways simultaneously present in the testicular niche that can modulate the effect of the inhibitors, leading to paradoxical effects. This investigation would help to better understand the interaction among pathway inhibitors and the cancer microenvironment and could allow for the prediction of responders and not-responders to TGTC personalized targeted therapies.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, the reported results of the NT2D1 cell invasion assays strongly indicate that the autologous microenvironment could positively or negatively modulate the cellular response to pathway inhibitors, and should be studied as a fundamental co-factor necessary for the success of inhibitor-based therapies. Taken together, these results indicate that the study of the testicular secretome of TGCT patients could be a useful tool to identify the possible interaction among PI3K inhibitors, i.e., those used for the targeted therapy proposed by [ 26 ] Selfe and coworkers, and the signaling pathways simultaneously present in the testicular niche that can modulate the effect of the inhibitors, leading to paradoxical effects. This investigation would help to better understand the interaction among pathway inhibitors and the cancer microenvironment and could allow for the prediction of responders and not-responders to TGTC personalized targeted therapies.…”
Section: Discussionmentioning
confidence: 78%
“…We previously demonstrated that NT2D1 cells do not express and secrete HGF [ 8 ]; therefore, as far as we know, there is not an autocrine contribution to c-MET activation in this cell line. In line with this result [ 25 , 26 ], Selfe and coworkers studied the constitutive phosphorylation of tyrosine-kinase receptors in TGCT-derived cell lines and concluded that the c-MET receptor is not constitutively activated in NT2D1 cells.…”
Section: Resultsmentioning
confidence: 86%
“…We studied c-MET and HGF expression even in seminoma and non-seminoma derived cell lines (TCam-2, NCCIT, NT2D1), demonstrating that HGF is not expressed by all these cell lines [4]. Accordingly, previous data from Selfe [6,7] and coworkers demonstrated that the c-MET receptor is expressed but not constitutively activated in the same cell lines. We also demonstrated that the non-seminoma cell line NT2D1 is the best responsive to the administration of exogenous HGF, with respect to TCam-2 and NCCIT cell lines [4].…”
Section: Introductionmentioning
confidence: 72%
“…Another proposed anticancer mechanism of Met points to the drug-induced modulation of specific mitogenic stimuli, such as insulin, IGFs and related binding proteins, leading to decreased activation of insulin/IGF receptors, and thus, reduced proliferation and progression of tumors dependent on these signaling pathways ( 7 ). The IGFs system has an essential role in the normal development and embryonic migration of PGCs, as well as in the tumorigenic process of these cells, including cisplatin-resistance and metastatic spread of male GCTs, often characterized by sustained activity of the IGF1R signaling pathway ( 55 ). In this context, the potential of Met as an effective adjuvant therapy reverting cisplatin-resistance in male GCTs, has recently been reported ( 56 ).…”
Section: Discussionmentioning
confidence: 99%